Metropolis - Lang, Fritz (Deutsche Universum Film AG, 1927)
Adapted from a novel by Lang's wife Thea Von Harbou, Metropolis combines the director's awe upon experiencing the hugeness of the New York City skyline with an H.G.Wellsian glance into the future. In the year 2000, the wealthy ruling class lives in towering luxury skyscrapers, while slave laborers monotonously toil away far below ground level. One man from the "rulers" dares to visit the underground where the workers toil, and is astonished by what he sees.